Size‐specific effects of bighead carp predation across the zooplankton size spectra. (16th April 2018) - Collins, Scott F.; Wahl, David H.
Abstract: Bigheaded carp (Cyprinidae: Hypophthalmichthys spp.) were brought to North America for aquaculture and eventually escaped captivity. Since their liberation, they have dispersed northward through the Mississippi River Basin and its tributaries. Although bigheaded carp are omnivorous filter‐feeding planktivores, their predatory effects on zooplankton are of principal concern because many native fishes feed on planktonic invertebrates during some phase of their life history. The aim of our study was to quantify the magnitude of effect of bighead carp ( Hypophthalmichthys nobilis ) on zooplankton body size and daily secondary production across a range of body lengths. We conducted an experiment where we compared responses of zooplankton in the presence of a native fish assemblage (control, n  = 5 ponds) and a native fish assemblage plus bighead carp (invaded, n  = 5 ponds). The experiment lasted 3 months (June–September, 2014) and was conducted in clay‐lined ponds (0.04 ha. wetted area; 1.5–1.75 m water depths). We quantified the predatory effects of bighead carp on overall changes to the size structure of zooplankton assemblages, body lengths of zooplankton taxa and taxa‐specific changes to standing crop biomass and daily secondary production. The size structure of zooplankton assemblage shifted towards smaller invertebrates in the presence of bighead carp. Bighead carp reduced the individual body sizes of Diaphanosoma (Sididae) (−19%) and Daphnia (Daphniidae) (−9%) after 3 months. Moreover, the standing crop biomass (−92% to 98%) and daily production (−65% to 74%) of Diaphanosoma, Daphnia and Calanoida were reduced in the presence of bighead carp. Bighead carp reduced immature copepod nauplii by 75% when compared to controls and may have affected recruitment to the adult stage. Our experiment indicated that the magnitude of predation by bighead carp increased with zooplankton body size, although rotifers and nauplii were exceptions to this pattern. The combined effects of reduced body sizes of some taxa and direct predation on immature and adult life stages of larger taxa suggest that bighead carp may be affecting zooplankton demographics through additional mechanisms such as reduced egg production, mate limitation, and recruitment.